Effectiveness of Ivermectin as A Treatment Modality for Cutaneous Larva Migrans: A Case Series - Dina Arwina Dalimunthe; Elza Wahyuni; Adina Miltania Tasmil; Regina Maharani Tambunan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cutaneous larva migrans (CLM) is a parasitic skin infection caused by the penetration of nematode larvae into the epidermis, typically following direct contact with contaminated soil or sand. The disease presents with characteristic serpiginous erythematous papules accompanied by intense pruritus and is commonly found in tropical regions with warm and humid climates. Although hookworm infection affects an estimated 740 million people globally, and Indonesia has a reported prevalence of 30–50%, ivermectin had not been used as a therapeutic option for CLM in Indonesia prior to the COVID-19 pandemic due to limited availability. The purpose of this report is to describe the clinical response of CLM patients treated with oral ivermectin as an alternative therapy that has only recently become accessible in Indonesia. This study was conducted as a descriptive case series. The respondents were three patients attending the dermatology outpatient clinic who were clinically diagnosed with cutaneous larva migrans. Data were obtained through patient interviews, dermatological examinations, dermoscopic evaluation, eosinophil counts, and clinical documentation before and after treatment. All patients received a single oral dose of 12 mg ivermectin. Three patients—two aged 67 years (one male and one female) and one 40-year-old female—presented with serpiginous erythematous papules accompanied by pruritus for 3 to 4 weeks. Two of them had previously shown no improvement with mebendazole and topical betamethasone. All patients demonstrated complete resolution of lesions after receiving a single 12 mg dose of ivermectin without any adverse effects. The results showed a 100% clinical cure rate across all cases, with no reported side effects following treatment. This case series highlights the effectiveness and safety of single-dose oral ivermectin for CLM and suggests that ivermectin may be considered a viable therapeutic option for the management of CLM in Indonesia.